Taxonomy of ’Euconnus complex’. Part XVI. Alloconophron Franz transferred to Anhoraeomorphus Franz as subgenus, with notes on systematic position of Noctophus Casey (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2017)
Based on examination of type species, Alloconophron, previously a subgenus of Euconnus, is placed as a subgenus of Anhoraeomorphus, resulting in Anhoraeomorphus (Alloconophron) grucheti (Franz) comb. n. and Anhoraeomorphus (Alloconophron) impressifrons (Franz) comb. n. All species of Anhoraeomorphus are known to occur in Madagascar. Noctophus stat. rest., a North American taxon originally described as a genus and later placed as a subgenus of Euconnus, is restituted as genus and redefined. Noctophus is morphologically surprisingly similar to Anhoraeomorphus, it also shares many structures with the Australo-Pacific Sciacharis. As Noctophus is known from one species represented by a single female holotype only, and the maxillary palps of this specimen are missing, the proposed placement of Noctophus is tentative and requires further study based on complete male specimens.